A systematic review of aggression and empathy (2024)
The evidence on the relationships between aggression and empathy is unclear in the literature. A recent meta- analysis indicated that associations are limited, while repeated research in recent years has reported both positive and negative correlations. This systematic review seeks to establish the current evidence on different studies that have been conducted on the relationships between proactive and reactive aggressive behavior and empathy, from the cognitive and affective subdomains, in adolescents, youth and young adults. Method: Systematic review according to PRISMA guidelines. Results: 8 articles were found that met the inclusion and exclusion criteria described and discrepancies between the associations of the two variables addressed are reported. Conclusion: there seems to be a certain degree of acceptance of the inhibitory role of empathy against aggression, particularly that of affective empathy. No conclusive results were found for cognitive empathy with the different types of aggression.